Diagnosis and Management Pancolitis in Patient with Ulcerative Colitis - Cindy Cindy; Riki Tenggara; Yudistira Panji Santoso; Mario Steffanus (The Indonesian Society for Digestive Endoscopy, 2010)
ABSTRACT Ulcerative colitis (UC) is a form of inflammatory bowel disease (IBD) that usually affects the rectum and part of the colon, which spreads continuously with no skip area. Pancolitis occurs in 20% of patients with UC. Patients with chronic UC, especially pancolitis, have a higher risk of colon cancer. In patients with pancolitis, the risk of cancer increases by 0.5-1% per year after having 8-10 years of disease. A 72-year-old man came with complaint of bloody-mucus diarrhea associated with abdominal cramps. The colonoscopic appearance of colitis was observed in whole lumen throughout colon. Histopathological analysis demonstrated dense infiltrates of granulocytes and macrophages formed by severe inflammation. Normal appearances were observed in the remaining epithelial cells. No parasites, specific process, or malignancy were found. Moreover, no acid-resistant bacteria were found. However, atypical cells were found in one of the biopsy specimens. The patient was diagnosed with extensive type of severe UC. The initial management of treatment included improvement of his general condition along with antibacterial therapy of metronidazole and ciprofloxacin. Specific treatment of sulphasalazine and prednisone were given after pancolitis appearance was revealed, which has similar clinical manifestations in accordance with UC. Keywords: pancolitis, ulcerative colitis, chronic diarrhea, inflammatory bowel disease